Soil aggregate stability under different Mediterranean vegetation types - Cerdà, A. (Catena, 1998)
The influence of vegetation type on soil erodibility was studied by means of aggregate stability measurements using the Modified Emerson Water Dispersion Test MEWDT , water-drop impacts . . . CND and TDI and Ultrasonic Disruption UD methods on soils from north-facing slopes of the mountain range of La Serra Grossa in the eastern Iberian Peninsula. Soils with similar characteristics but covered by the main plant species at the study area were selected. Quercus ilex woodland showed the most resistant soil aggregates followed by Q. coccifera and Pistacea lentiscus scrubland, Brachypodium retusum grassland and Pinus halepensis woodland. Aggregates developed beneath dwarf shrubs like Rosmarinus officinalis, Thymus Íulgaris, Ulex parÍiflorus and Anthyllis cystisoides were least resistant. The different methods and tests applied are useful to study the soil aggregate stability. The MEWDT and TDI tests showed only minor differences between samples due to the high aggregate resistance and the low energy applied by these tests. CND and UD tests are considered to be more suitable for resistant Mediterranean soil developed on limestone due to the greater energy applied. Aggregates tested from an initially moist pF1 condition were always more stable than air dried aggregates. Rangeland management . after disturbances by fire, agriculture or grazing, etc. should try to establish natural woodland Q. ilex. in order to get the most stable soil. Alternative vegetation cover to the climax vegetation that give high aggregate stability are Q. coccifera and P. lentiscus scrublands. Immediately after disturbance, B. retusum grassland seems to be the best option for soil protection.
Keywords: Aggregate stability; Laboratory test; Mediterranean; Vegetation